AIR TRAFFIC FLOW MANAGEMENT – ATFM (Perner's Contacts, 2018)
ATFM - Air Traffic Flow Management is an organized service as a part of Air Traffic Management (ATM). ATFM is provided for aircrafts and air carriers to ensure controlled safe economic and regular flight operation. There are many factors either expected or accidental which have influence to ATFM. We have to take into account all these factors especially negative ones. Therefore we perceive the ATFM as a tool to reduce the effect of these influences even to their maximum elimination. ATFM - Air Traffic Flow Management we can imagine as the coordinated activities of individuals or operational segments involved in the process of air traffic in order to optimize the process of Flight Management. The output of these activities is to ensure a safe, economy and smooth air traffic.
Keywords: Operations Manager, Flow Management, Capacity, Planning, Slot